Clinical and Genetic Characteristics of ABCC8 Nonneonatal Diabetes Mellitus: A Systematic Review. (30th September 2021) - Li, Meng; Han, Xueyao; Ji, Linong
Abstract : Objectives . Diabetes mellitus (DM) is a major chronic metabolic disease in the world, and the prevalence has been increasing rapidly in recent years. The channel of KATP plays an important role in the regulation of insulin secretion. The variants in ABCC8 gene encoding the SUR1 subunit of KATP could cause a variety of phenotypes, including neonatal diabetes mellitus ( ABCC8- NDM) and ABCC8 -induced nonneonatal diabetes mellitus ( ABCC8 -NNDM). Since the features of ABCC8 -NNDM have not been elucidated, this study is aimed at concluding the genetic features and clinical characteristics. Methods . We comprehensively reviewed the literature associated with ABCC8 -NNDM in the following databases: MEDLINE, PubMed, and Web of Science to investigate the features of ABCC8 -NNDM. Results . Based on a comprehensive literature search, we found that 87 probands with ABCC8 -NNDM carried 71 ABCC8 genetic variant alleles, 24% of whom carried inactivating variants, 24% carried activating variants, and the remaining 52% carried activating or inactivating variants. Nine of these variants were confirmed to be activating or inactivating through functional studies, while four variants (p.R370S, p.E1506K, p.R1418H, and p.R1420H) were confirmed to be inactivating. The phenotypes of ABCC8 -NNDM were variable and could also present with early hyperinsulinemia followed by reduced insulin secretion, progressing to diabetes later. They had a relatively high risk of microvascular complications and low prevalence of nervous disease, which is different from ABCC8- NDM. Conclusions . Genetic testing is essential for proper diagnosis and appropriate treatment for patients with ABCC8 -NNDM. And further studies are required to determine the complex mechanism of the variants of ABCC8 -NNDM.